SEP spectra derived from neutron monitor data and from EPHIN space detector data during recent GLEs and sub-GLEs - Bütikofer, Rolf; Kühl, Patrick; Papaioannou, Athanasios (2021)
The Electron Proton Helium Instrument (EPHIN) aboard the Solar Heliospheric Observatory (SOHO) observed several SEP events with protons accelerated to energies E>500 MeV, whereas no neutron monitor (NM) of the worldwide network showed a significant increase in their counting rate. For instance, the SEP event on 8 November 2000 with maximum proton intensity at 500 MeV of >0.1 (cm2 s sr MeV)-1 is outstanding, as this maximum pro-ton flux is comparable with the GLEs on 14 July 2000 and on 15 April 2001 (max. count rate increase in 5-min data of 225% at South Pole NM). In a first step we applied a forward modelling approach of the SEP event on 8 November 2000, i.e. we computed the expected NM count rate increases for selected NM stations, utilizing as input para-meters the SEP spectra determined from EPHIN data as well as anticipated pitch angle distribution and apparent source direction. The simulated count rate increases for selected NM stations showed that this SEP event should have be seen as a clear GLE. To further understand this situation, we investigated in a next step recent GLEs and sub-GLEs. Consequently, a total of four SEP events were selected, two clearly identified GLEs and two sub-GLEs. We performed a “GLE analysis” based on the data of the worldwide network of NMs for each of the four SEP events and then compared the derived SEP spectra with the proton spectra as determined from EPHIN measurements.